Distinguishable Prognostic miRNA Signatures of Head and Neck Squamous Cell Cancer With or Without HPV Infection - Luo, Xiao-jie; Zheng, Min; Cao, Ming-xin; Zhang, Wei-long; Huang, Mei-chang; Dai, Li; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Oncology, 2021)
Since their discovery in the 1990's,microRNAs(miRNA) have opened up new vistas in the field of cancer biology and are found to have fundamental roles in tumorigenesis and progression. As head and neck squamous cell carcinoma(HNSCC) with positive human papillomavirus (HPV+) is significantly distinct from its HPV negative(HPV-) counterpart in terms of both molecular mechanisms and clinical prognosis,the current study aimed to separately develop miRNA signatures for HPV+ and HPV- HNSCC as well as to explore the potential functions. Both signatures were reliable forthe prediction of prognosis in their respective groups. Then Enrichment analysis was performed to predict the potential biological functions of the signatures.Importantly,combining previous studies and ourresults,we speculated that HPV+ HNSCC patients with low signature score had better immunity against the tumors and enhanced the sensitivity of therapies leading to improved prognosis,while HPV- HNSCC patients with high signature score acquired resistance to therapeutic approaches as well as dysregulation of cell metabolism leading to poor prognosis. Hence,we believe that the identified signatures respectively for HPV+ and HPV- HNSCC,are of great significance in accessing patient outcomes as well as uncovering new biomarkers and therapeutic targets,which are worth further investigation through molecular biology experiments.